Promotion of Local Deworming Medicine Utilization Through Vlog Media to Shape Healthy Perceptions Among At-Risk Groups - Irma, Irma; Salakory, Melianus; Tetelepta, Edward Gland (Jurnal Pendidikan Geografi Unpatti, 2022)
Promotions are submitted or disseminating. The main purpose in promotion is to create an effective message / information to attract customer's attention. Based on these circumstances, currently YouTube is not only for use as an entertainment needs, but also as a social media that believe in the level of Internet users are quite a lot. This research uses exploration method and qualitative case study approach.. The subject of the research is the basic material of medicine, YouTube and children's risk group. This research is carried out in the gigorate education gigchiography laboratory for the manufacture of viors and kelurahan Waihaong to get children's risk groups.Research Results of the promotion of local utilization of drug-based worms by utilizing vlog media in an effort to form a group of healthy perceptionsthe risk ofie Cookies products of Chinese maps and Cookies Sweet Kasbi Ostar which is said to pass the test of the experience of the spirit of the worm in children and formed healthy perceptions in the risk